Design Concept of Power Stockings - Ghosal, Arindam; Patil, Pravin P.; Rawat, Nitesh; Gusain, Gaurav (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*317.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918531);" role="presentation">This paper presents the experimental design <span dir="ltr" style="left: calc(var(--scale-factor)*256.25px); top: calc(var(--scale-factor)*317.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.890377);" role="presentation">concept <span dir="ltr" style="left: calc(var(--scale-factor)*290.93px); top: calc(var(--scale-factor)*317.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924589);" role="presentation">of an energy harvesting system that uses the mech<span dir="ltr" style="left: calc(var(--scale-factor)*499.54px); top: calc(var(--scale-factor)*317.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917912);" role="presentation">anical <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*330.41px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.912809);" role="presentation">energy of our body to generate and store electricity for further use. It uses active elements to generate electricity <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*343.73px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.961382);" role="presentation">from the base of our stockings, it uses piezoelectric elements. While walking there it will be the mechanical <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*356.93px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918509);" role="presentation">stress in piezo eleme<span dir="ltr" style="left: calc(var(--scale-factor)*158.18px); top: calc(var(--scale-factor)*356.93px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941145);" role="presentation">nt, when this stress is released then there would be the production of the electric charge <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*370.13px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.947245);" role="presentation">which will be harvested in the flexible battery attached to the stocking. The electric energy processing will be <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*383.33px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.908313);" role="presentation">maintained by using energy harvesting module